Who Plays With Whom: Farrowing Environment Influences Isolation of Foster Piglets in Play - Clarkson, Jasmine M.; Baxter, Emma M.; Martin, Jessica E. (Frontiers in Animal Science, 2021)
Cross fostering piglets is a common management practice in the pig industry to manage large and heterogeneous litters, whereby piglets are moved from their biological litter to be reared by another sow. At present research has focused on immediate survival consequences and time of cross fostering, with little attention given to positive aspects of welfare such as social affiliations and the potential for positive interactions for these piglets such as play behaviour. The focus of our study was purely observational to record behaviour of piglets reared in either impoverished (farrowing crates) or enriched neonatal environments (PigSAFE pens) where fostering was practiced as part of normal husbandry routines to promote piglet survival. We employed social network analysis to understand more about the behaviour of foster piglets in these environments and their acceptance into their new litter. In line with previous work, piglets exposed to enriched neonatal farrowing pens demonstrated more play behaviour than piglets reared in farrowing crates. We showed that pen piglets received and initiated more play invitations (higher degree centrality) than piglets in crates. We also found effects of cross fostering irrespective of neonatal environment. Non-foster piglets received and initiated more play behaviours (higher degree centrality) 2-3 weeks post-farrowing compared to piglets fostered into the litter and as such, fostered piglets remained isolated from play for the first few weeks of life. However, our data suggests this may be mitigated by neonatal environment; foster piglets reared in pens were better connected (betweenness centrality) within their foster litter than those fostered in crates. Our findings highlight the importance of neonatal environment and its potential influence on the isolation of cross-fostered piglets and suggest that rearing in enriched neonatal environments may help mitigate against social isolation in early life of cross-fostered piglets, having obvious immediate and long-term consequences for piglet welfare and behaviour. We also highlight the importance and application of methodologies such as social network analysis, for gaining more insight and understanding about the sociality of animal behaviour and its potential for measuring indicators of positive welfare, thus highlighting its application for veterinary science and animal behaviour and welfare research.